2021
DOI: 10.1111/spsr.12458
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Policy Responses to the COVID‐19 Pandemic in Switzerland

Abstract: We study the role of social media in debates regarding two policy responses to COVID‐19 in Switzerland: face‐mask rules and contact‐tracing apps. We use a dictionary classifier to categorize 612'177 tweets by parties, politicians, and the public as well as 441'458 articles published in 76 newspapers between February and August 2020. We distinguish between “problem” (COVID‐19) and “solutions” (face masks and contact‐tracing apps) and, using a vector autoregression approach, we analyze the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Another aspect is that social media may restrict traditional elites from communicating policy measures. The debate on face masks on Twitter in Switzerland was found to be driven by individual politicians and the public, whereas parties and newspapers picked up Twitter debates (Gilardi et al, 2021). Non-expert voices on social media that emerged after the crisis phase of the pandemic decreased the public's trust in institutions (van Dijck and Alinejad, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is that social media may restrict traditional elites from communicating policy measures. The debate on face masks on Twitter in Switzerland was found to be driven by individual politicians and the public, whereas parties and newspapers picked up Twitter debates (Gilardi et al, 2021). Non-expert voices on social media that emerged after the crisis phase of the pandemic decreased the public's trust in institutions (van Dijck and Alinejad, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…VAR models explain the change over time of multiple variables based on their own lagged values as well as the lagged values of the other variables incuded in the model, which allows us to analyze the relationships between several variables over time. VAR models are well suited to capture the process between endogenous variables and have been used by similar studies (Barberá et al, 2019;Edwards & Wood, 1999;Gilardi et al, 2021bGilardi et al, , 2021cWood & Peake, 1998). Specifically, our model mirrors the design of Barberá et al (2019), who uses a VAR model with a set of stationary time series Y i representing the share of the daily attention each group i paid to the topics j of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, government communication during crises is most effective when it translates scientific and technical information (Herovic et al, 2020). Gilardi, Gessler, Kubli, and Müller (2021) further found that social media challenge the capacity of party and media elites to craft a consensus regarding the appropriateness of different measures as responses to COVID-19.…”
Section: The Role Of Social Media In Crisis Communicationmentioning
confidence: 99%
“…However, social media also challenge political authorities' communication, as they allow multiple stakeholders and groups to shape social and political agendas while bypassing traditional gatekeepers such as news media (Jungherr & Gayo-Avello, 2020). For instance, Gilardi et al (2021) investigated policy responses to COVID-19 promoted by Swiss political and health authorities, with a special focus on policy solutions, namely, face mask rules and contact tracing apps. The authors analysed the salience of these policy solutions to the COVID-19 problem.…”
Section: The Role Of Social Media In Crisis Communicationmentioning
confidence: 99%